Avaliação da palma forrageira em diferentes densidades de plantio - Cavalcante, Lucas Aroaldo Dantas (2013)
The experiment was conducted at the Experimental Center of the Coastal Plains Agricultural Research - CPATC - Embrapa, in Frei Paulo - SE to evaluate the morphology, chemical composition and productivity of forage cultivars in different planting densities. The experimental design was a randomized block in factorial 3X4. The treatments consisted of a combination of three species of cactus pear (Palma Giant and Tiny Round), four planting densities (10,000, 20,000, 40,000 and 80,000 plants.ha-1), with three replications. The sample collection was performed at 24 months after planting, and evaluated the morphometric measurements, production and chemical composition in each treatment. The species of forage presented different behaviors regarding morphometry, productivity and chemical composition and independent of the kind denser planting increases productivity and provides greater accumulation of water and nutrients per hectare2 years.